Dekonstrukcja podmiotu według feministycznej jurysprudencji - Rodak, Lidia (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper addresses some of the fundamental aspects of the deconstruction of law and, in particular, the deconstruction of the legal subject from the perspective of feminist jurisprudence. It introduces the main problems of masculinisation of the legal subject and its consequences for the legal discourse. I wish to begin by reconstructing the history of the feminist deconstruction of the subject, with the special focus on its philosophical roots, which is necessary to explain the process of the subject’s masculinisation. In what follows, I present S. Bordo’s theory of the “Cartesian moment” and contrast it with M. Foucault’s view on the transformation of the subject in the history of philosophy. I finally arrive at the analysis of the legal discourse, with the special focus on the conception of the legal subject. The aim of the analysis is to point out that the process of masculinisation is deeply rooted and well-fixed in the legal narrative. I conclude with an assessment of Bordo’s and Foucault’s views, claiming that their insightful theories identify the conception of the “rational man” as the core problem within the legal discourse.
Keywords: dekonstrukcja prawa; orzecznictwo feministyczne; Foucault, Michael (1926-1984); Bordo, Susan